Pembangkit Sinyal ELT pada Frekuensi 121,5 MHz - Rustamaji, Rustamaji; Sawitri, Kania; Sitepu, Ray Hapri (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2019)
An ELT is a beacon indicating the location of distress or crash of aircraft on land or sea. The ELT is placed in an airplane, which is a transmitter with low transmit power and an antenna. The ELT transmitter has been widely used for flights at the frequency of 121.5 MHz (civilian) and 243 MHz (military). The purpose of this study is to produce ELT signal generators at the 121.5 MHz frequency, with low-cost devices that meet specifications for civil aviation. In this research has been produced a design of an ELT signal generator at the frequency of 121.5 MHz, consist of a crystal oscillator, a sawtooth generator, a VCO, and an amplitude modulator. Based on the measurement and test results, the sawtooth generator generated a sawtooth signal at the frequency of 1.8 to 3.6 Hz, the VCO generated a sinusoidal signal at the frequency of 316 to 366 Hz, the RF generator generated a sinusoidal at the frequency of 121.505 MHz. The ELT signal generator was able to generate AM signals at the minimum amplitude deviation of 100 mVpp to maximum one of 156 mVpp, the modulation index (m) of 21.875%, and the frequency of 121.505 MHz. The results of this study are ELT signal generators at the frequencies of 121.5 MHz that are in accordance with specifications for civil aviation.